Review of the idiocerine leafhoppers of Pakistan (Hemiptera, Cicadellidae) with a description of a new species - Khatri, Imran; Webb, M. D. (Zootaxa, 2014)
The Idiocerinae of Pakistan are reviewed and a new species, Tasnimocerus sindhensis sp. nov. (Pakistan: Tandojam), is described and illustrated from Pakistan. Two new junior synonyms of Idioscopus nitidulus (Walker) are recognized: Idioscopus karachiensis Ahmed, Naheed & Ahmed syn. nov. and I. freytagi Ahmed, Naheed & Ahmed syn. nov. Idioscopus nagpurensis (Pruthi) is newly recorded from Pakistan. A checklist of Idiocerinae from Pakistan is also provided together with a key to genera and species.